Reliability and validity of brief psychosocial measures related to dietary behaviors - Calfas Karen J; Wagner Nicole; Sallis James F; Carlson Jordan A; Norman Gregory J; Patrick Kevin (BMC, 2010)
Abstract Background Measures of psychosocial constructs are required to assess dietary interventions. This study evaluated brief psychosocial scales related to 4 dietary behaviors (consumption of fat, fiber/whole grains, fruits, and vegetables). Methods Two studies were conducted. Study 1 assessed two-week reliability of the psychosocial measures with a sample of 49 college students. Study 2 assessed convergent and discriminant validity of the psychosocial measures with dietary nutrient estimates from a Food Frequency Questionnaire on 441 men and 401 women enrolled in an Internet-based weight loss intervention study. Results Study 1 test-retest reliability ICCs were strong and ranged from .63 to .79. In study 2, dietary fat cons, fiber/whole grain cons and self-efficacy, fruit and vegetable cons and self-efficacy, and healthy eating social support, environmental factors, enjoyment, and change strategies demonstrated adequate correlations with the corresponding dietary nutrient estimates. Conclusions Brief psychosocial measures related to dietary behaviors demonstrated adequate reliability and in most cases validity. The strongest and most consistent scales related to dietary behaviors were healthy eating change strategies and enjoyment. Consistent convergent validity was also found for the cons of change scales. These measures can be used in intervention studies to evaluate psychosocial mediators of dietary change in overweight and obese individuals.